Time in Television Narrative : Exploring Temporality in Twenty-First-Century Programming - Ames, Melissa, 1978- (Book collections on Project MUSE., 2012)
This collection analyzes twenty-first-century American television programs that rely upon temporal and narrative experimentation. These shows play with time, slowing it down to unfold the narrative through time retardation and compression. They disrupt the chronological flow of time itself, using flashbacks and insisting that viewers be able to situate themselves in both the present and the past narrative threads. Although temporal play has existed on the small screen prior to the new millennium, never before has narrative time been so freely adapted in mainstream television. The essayists off.